Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1534/genetics.114.161430
|View full text |Cite
|
Sign up to set email alerts
|

NsdD Is a Key Repressor of Asexual Development inAspergillus nidulans

Abstract: Asexual development (conidiation) of the filamentous fungus Aspergillus nidulans occurs via balanced activities of multiple positive and negative regulators. For instance, FluG (+) and SfgA (2) govern upstream regulation of the developmental switch, and BrlA (+) and VosA (2) control the progression and completion of conidiation. To identify negative regulators of conidiation downstream of FluG-SfgA, we carried out multicopy genetic screens using sfgA deletion strains. After visually screening .100,000 colonies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
81
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 69 publications
2
81
0
1
Order By: Relevance
“…In addition, nearly all late light response genes are misregulated in the loss‐of‐function sub‐1 mutant in a white collar complex‐dependent manner (Chen et al ., ). This role in N. crassa is also consistent with the reported function of the A. nidulans NsdD orthologue as a positive regulator of sexual development and component of the endogenous regulatory circuit including brlA , rosA , nosA and nsdB functioning to balance asexual and sexual development (Han et al ., ; Lee et al ., ). Given the positive roles of Sub‐1 orthologues in light‐responsive sexual development, we hypothesized that loss‐of‐function Δ Ssnsd1 mutants would exhibit phenotypes associated with light‐dependent apothecium development.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, nearly all late light response genes are misregulated in the loss‐of‐function sub‐1 mutant in a white collar complex‐dependent manner (Chen et al ., ). This role in N. crassa is also consistent with the reported function of the A. nidulans NsdD orthologue as a positive regulator of sexual development and component of the endogenous regulatory circuit including brlA , rosA , nosA and nsdB functioning to balance asexual and sexual development (Han et al ., ; Lee et al ., ). Given the positive roles of Sub‐1 orthologues in light‐responsive sexual development, we hypothesized that loss‐of‐function Δ Ssnsd1 mutants would exhibit phenotypes associated with light‐dependent apothecium development.…”
Section: Discussionmentioning
confidence: 97%
“…2). Previous genetic analyses have demonstrated that the overexpression of hbxD suppresses fungal growth and asexual development, suggesting that HbxD is required for the proper development 50 . The orthologs of HbxD have been studied in other fungi, such as M. oryzae and C. albicans.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report provided experimental evidence of a functional link between the UDA pathway and the positive regulator of sexual development NsdD (Lee et al 2014). Because nsdD deletion bypassed the need of UDAs (but not CDPs) for conidia production, the authors proposed that NsdD also down-regulated brlA expression to inhibit the asexual program.…”
Section: Discussionmentioning
confidence: 99%
“…Graphs were obtained with Microsoft Excel, and the average pixel intensity for each band was calculated with Image Gauge (version 4.0; Fujifilm, Valhalla, NY). Lee et al (2014) have recently proposed that Flbs induce conidiation by simultaneously suppressing the brlA downregulation caused by NsdD, a positive regulator of cleistothecia production (Han et al 2001). To analyze whether the genetic relationship between Flbs and NsdD could be established through UrdA, we performed new Northern blot experiments.…”
Section: Global Analysis Of Flbb Activity In the Regulation Of Genes mentioning
confidence: 99%